2012
DOI: 10.1007/s10853-012-6263-z
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the stress induced martensitic formation in titanium alloys by alloy design

Abstract: Two novel titanium alloys, Ti-10V-2Cr-3Al and Ti-10V-1Fe-3Al (wt%), have been designed, fabricated, and tested for their intended stress-induced martensitic (SIM) transformation behavior. The results show that for Ti-10V-1Fe-3Al the triggering stress for SIM transformation is independently affected by the b domain size and b phase stability, when the value of the molybdenum equivalent is higher than *9. The triggering stress was well predicted using the equations derived separately for the commercial Ti-10V-2F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 26 publications
(33 reference statements)
1
27
0
1
Order By: Relevance
“…The factors are: (i) the stability of the b phase, i.e., the chemical composition of b phase, and (ii) b domain size (in our study it is defined as the remaining b surrounded by a before compression). These two aspects vary with the a phase fraction [24,25,28]. The authors of Refs.…”
Section: Formation Of Stress-induced a 00 Martensite And Correspondinmentioning
confidence: 99%
See 3 more Smart Citations
“…The factors are: (i) the stability of the b phase, i.e., the chemical composition of b phase, and (ii) b domain size (in our study it is defined as the remaining b surrounded by a before compression). These two aspects vary with the a phase fraction [24,25,28]. The authors of Refs.…”
Section: Formation Of Stress-induced a 00 Martensite And Correspondinmentioning
confidence: 99%
“…The authors of Refs. [24,25,28] reported that with an increasing amount of a, b phase becomes more stable while b domain size decreases. Both events oppose stress-induced a 00 martensite formation, as chemically stable b tends to hinder b !…”
Section: Formation Of Stress-induced a 00 Martensite And Correspondinmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that for values of higher than 8 wt.%, the β phase will be in a metastable state and is likely to transform into α″ phase under applied stress [123]. A three step deformation sequence of martensitic transformation was established in previous studies [5].…”
Section: 2mentioning
confidence: 98%